2009
DOI: 10.1260/0309-524x.33.6.587
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Risk of a Failed Wind Turbine Blade Impacting a Power Transmission Line

Abstract: Wind turbine installations are generally situated in proximity to power transmission lines that integrate generated power into the grid. Failure of a wind turbine that results in a blade or blade fragment thrown from the rotor can result in impact with a transmission line and lead to significant transmission line damage. The work reported here creates a mathematical model to assess the risk of this type of failure event occurring as a function of wind turbine characteristics and the relative position of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Five Monte Carlo simulations consisting of 10,000 blade throws each were performed for each turbine, corresponding to the five blade fragment sizes of 20, 40, 60, 80 and 100% as previously outlined. As demonstrated in the Monte Carlo simulation results shown in Slegers, smaller blade fragments consistently fly farther than larger fragments because of higher initial release velocity. Figures show ground impact results of each Monte Carlo simulation for the three turbines for the 40% blade throw case.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five Monte Carlo simulations consisting of 10,000 blade throws each were performed for each turbine, corresponding to the five blade fragment sizes of 20, 40, 60, 80 and 100% as previously outlined. As demonstrated in the Monte Carlo simulation results shown in Slegers, smaller blade fragments consistently fly farther than larger fragments because of higher initial release velocity. Figures show ground impact results of each Monte Carlo simulation for the three turbines for the 40% blade throw case.…”
Section: Resultsmentioning
confidence: 99%
“…An abbreviated version of the dynamic model used to simulate the flight of a released blade fragment is presented here. A full description of the dynamic model can be found in Slegers et al As shown in Figures and , three reference frames are employed in the dynamic model of blade motion, namely, the ground‐based frame I, the turbine‐fixed frame R and the blade‐fixed frame B. The blade‐fixed reference frame B is oriented such that the KB axis is aligned with the blade spanwise axis.…”
Section: Dynamic Model and Simulation Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The next level of complexity has fragment rotation and translation along the trajectory, with calculation of aerodynamic forces and moments (Slegers et al, 2009). The authors' trajectory model is based primarily on Sørensen (1984).…”
Section: Fragment Trajectorymentioning
confidence: 99%